Analyzing Consumer Perceived Value on MOBA Mobile Games To Increase Mobile Game Loyalty And In-App Purchase Intention (Journal of Business and Management, 2022)
The meteoric rise of the mobile gaming industry is not paired with the ability of its developer to induce its players’ loyalty and ultimately purchase intention. Understanding the influential factors of what makes a customer loyal and making a purchase is important for the developers as it would increase the profit margin. The purpose of this study is to investigate the customer’s perceived value that influences mobile game loyalty and in-app purchase, or purchase made within the game, for MOBA (Multiplayer Online Battle Arena) mobile game players. The data gathered in order to fulfill the research objective is done by both conducting qualitative preliminary research and distributing quantitative online questionnaires (which successfully gathered 205 respondents, mostly male and undergraduate students) on various social media platforms. It was then analyzed through PLS-SEM analysis, and results of the analysis shows that the customer perceived value that significantly influences mobile game loyalty are reward, access flexibility and playfulness, while good price and mobile game loyalty are the significant influential factors that drive in-app purchase intention. Additionally, recommendations from the researcher based on the influential factors that have been found in this research have been described as well, and future practitioners might look at it as a consideration for their research or business strategy as well.Keywords: Customer Perceived Values, Indonesian MOBA In-app Purchase Intention, Indonesian MOBA Mobile Game Loyalty, MOBA Mobile Game